2017
DOI: 10.1308/rcsann.2017.0083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the quantity of intradiscal cement leak on the progression of intervertebral disc degeneration

Abstract: Introduction We aim to assess the impact of the quantity of intradiscal cement leak during kyphoplasty on the rate of progression of degenerative changes in the affected disc. Methods Of 316 kyphoplasty procedures, we identified 32 episodes of intradiscal cement leak in 26 patients. The quantity of cement leaked was graded from I to IV. Disc degenerative changes were assessed at presentation and follow-up using radiographical scoring and magnetic resonance imaging (MRI) grading systems. Data for low-grade leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
(28 reference statements)
2
11
1
1
Order By: Relevance
“…When bone cement leaks to the other endplate, recompression of the vertebral body on the one hand may lead to spinal balance, local kyphosis, and thus chronic pain [23,24]. However, our study found no signi cant difference in AVHR and LKA among the groups, only statistically signi cant relative to preoperative.…”
Section: Discussioncontrasting
confidence: 70%
“…When bone cement leaks to the other endplate, recompression of the vertebral body on the one hand may lead to spinal balance, local kyphosis, and thus chronic pain [23,24]. However, our study found no signi cant difference in AVHR and LKA among the groups, only statistically signi cant relative to preoperative.…”
Section: Discussioncontrasting
confidence: 70%
“…While some studies reported that the leakage did not induce adjacent vertebral body collapse 41,42 , others obtained opposite results 43 . In the meantime, many studies revealed that bone cement may be toxic to the intervertebral disc and that it accelerates degeneration [44][45][46] . In our study, we did not observe a higher rate of adjacent segment fracture for the high-viscosity cement group, despite its higher intradiscal leakage rate.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of intradiscal cement leaked was quanti ed by a grading system proposed by two of the authors Z Klezl and S Patel classi cation (ZK and SP). [21] They proposed that grade I when cement leakage into the disc space was minimal / cloud, grade II when cement leakage lled <20% of the disc space, grade III when cement leakage lled 20-40% of the disc space and grade IV when cement leakage lled >40% of the disc space.…”
Section: X-ray and Ct Scan Evaluationmentioning
confidence: 99%